A PENGARUH MOTIVASI BELAJAR DAN DUKUNGAN KELUARGA TERHADAP MINAT SISWA MEMILIH JURUSAN KEAGAMAAN: PENGARUH MOTIVASI BELAJAR DAN DUKUNGAN KELUARGA TERHADAP MINAT SISWA MEMILIH JURUSAN KEAGAMAAN - Sumantri; Permana, Galih; Nurhayati, Nurhayati (Epistemic: Jurnal Ilmiah Pendidikan, 2025)
The declining interest of students in selecting the Islamic Religious Studies major at State Islamic Senior High Schools (MAN) in Sukabumi Regency raises concerns about the sustainability of Islamic education pathways. This study aims to examine the influence of learning motivation and family support on students’ interest in choosing this major. A quantitative approach with a descriptive-correlational design was employed. A sample of 194 eleventh-grade students from three MAN institutions was selected using the Taro Yamane formula and simple random sampling technique. Data were collected through a Likert-scale questionnaire and analyzed using correlation and multiple regression analysis via SPSS version 23. The findings revealed that learning motivation contributed 15.9%, family support contributed 19.3%, and both variables jointly explained 24.6% of the variance in students’ interest. These results highlight the significance of psychosocial factors in educational decision-making. The study underscores the practical need to strengthen family involvement and enhance students’ intrinsic motivation to support the continuity of Islamic Religious Studies programs. Further research is recommended to incorporate broader variables and extend the geographic scope for a more comprehensive understanding of the issue.